2015
DOI: 10.1371/journal.pone.0116332
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Vascular Endothelial Growth Factor A (VEGFA) Isoforms in Granulosa Cells Using pDmrt-1-Cre or Amhr2-Cre Reduces Fertility by Arresting Follicular Development and by Reducing Litter Size in Female Mice

Abstract: Because VEGFA has been implicated in follicle development, the objective of this study was to determine the effects of granulosa- and germ cell-specific VEGFA loss on ovarian morphogenesis, function, and female fertility. pDmrt1-Cre mice were mated to floxed VEGFA mice to develop granulosa-/germ cell-specific knockouts (pDmrt1-Cre;Vegfa -/-). The time from mating to first parturition was increased when pDmrt1-Cre;Vegfa -/- females were mated to control males (P = 0.0008) and tended to be longer for heterozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Hypoxia has been shown to upregulate vascular endothelial growth factor (VEGF) in the swine granulosa cell (Basini et al, 2004). VEGF induces expression of 17ß-estradiol in mice granulosa cells and is a key mediator of follicle maturation (Sargent et al, 2015). Therefore, it is possible that our observation of increased estradiol in hypoxic rats is a result of increased VEGF or another similar factor, occurring independently of a rise in FSH.…”
Section: The Effect Of Flutamide On Granulosa Cell Functionmentioning
confidence: 92%
“…Hypoxia has been shown to upregulate vascular endothelial growth factor (VEGF) in the swine granulosa cell (Basini et al, 2004). VEGF induces expression of 17ß-estradiol in mice granulosa cells and is a key mediator of follicle maturation (Sargent et al, 2015). Therefore, it is possible that our observation of increased estradiol in hypoxic rats is a result of increased VEGF or another similar factor, occurring independently of a rise in FSH.…”
Section: The Effect Of Flutamide On Granulosa Cell Functionmentioning
confidence: 92%
“…Apoptosis and proliferation are crucial cellular physiological processes during ovarian follicular development [9,[37][38][39]. Notably, the crosstalk between cell death and survival signals is vital in regulating follicular cellular development and ultimately determines whether the follicles undergo atresia or ovulation, which is regulated by several ovarian factors [9,40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show the presence of VEGFA in follicular fluid of cattle (Berisha et al, 2000(Berisha et al, , 2008Grazul-Bilska et al, 2007), pigs (Mattioli et al, 2001;Galeati et al, 2003), and humans (Friedman et al, 1997;Coppola et al, 2005) as well as the ability of bovine (Schams et al, 2001), primate (Duffy and Stouffer, 2003), and porcine (Galeati et al, 2003;Grasselli et al, 2010) GC from antral follicles to produce VEGFA in vitro. More recently, a study in mice showed that loss of VEGFA gene expression in GC arrests follicular development leading to decreased fertility (Sargent et al, 2015). However, the hormones and growth factors that regulate follicular VEGFA production in cattle is unknown, and therefore, additional studies are required to determine the hormonal control of VEGFA production in bovine GC and TC.…”
Section: Introductionmentioning
confidence: 99%